Faktor Psikologis dalam Manajemen: Meningkatkan Kesejahteraan, Motivasi, dan Kinerja di Institusi Pendidikan dan Organisasi - Raisa Fattimatuz Z; Chofifatul Jamilah; Muhammad Sultan M; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Psychological well-being in the workplace and educational environment is influenced not only by policies and facilities but also by psychological approaches that touch on individuals' mental, emotional, and spiritual aspects. This study aims to explain how psychological approaches can enhance well-being and motivation. The results of the study show that integrating Islamic educational values, mindfulness, and emotional intelligence can help individuals manage stress, increase self-confidence, and strengthen the meaning of life. In addition, adjusting learning materials to the needs of students also plays a role in supporting mental health. Individual motivation can be increased through approaches that align with psychological needs, such as fulfilling basic needs, providing rewards, and supporting autonomy and social relationships. The implementation of strategies such as open communication, good leadership, and a comfortable work environment also contributes to increasing motivation and performance. Thus, the psychological approach has an important role in creating a healthy, productive, and sustainable educational and organizational environment.